Biological and evolutionary significance of terminal extensions of mitochondrial translation initiation factor 3 - Derbikova, Ksenia; Kuzmenko, Anton; Levitskii, Sergey; Klimontova, Maria; Chicherin, Ivan; Baleva, Maria V.; Krasheninnikov, Igor A.; Kamenski, Piotr (International journal of molecular sciences, 2018)
Protein biosynthesis in mitochondria is organized in a bacterial manner. However, during evolution, mitochondrial translation mechanisms underwent many organelle-specific changes. In particular, almost all mitochondrial translation factors, being orthologous to bacterial proteins, are characterized by some unique elements of primary or secondary structure. In the case of the organellar initiation factor 3 (IF3), these elements are several dozen amino acids long N- and C-terminal extensions. This study focused on the terminal extensions of baker’s yeast mitochondrial IF3, Aim23p. By in vivo deletion and complementation analysis, we show that at least one extension is necessary for Aim23p function. At the same time, human mitochondrial IF3 is fully functional in yeast mitochondria even without both terminal extensions. While Escherichia coli IF3 itself is poorly active in yeast mitochondria, adding Aim23p terminal extensions makes the resulting chimeric protein as functional as the cognate factor. Our results show that the terminal extensions of IF3 have evolved as the “adaptors” that accommodate the translation factor of bacterial origin to the evolutionary changed protein biosynthesis system in mitochondria.